ANALISIS PENGARUH FAKTOR PENYEBAB NON-EXCUSABLE DELAY PADA PROYEK KONSTRUKSI GEDUNG DI MANADO - Stevie Andrean; I Putu Artama Wiguna; Tri Joko Wahyudi (Institut Teknologi Sepuluh Nopember (ITS), 2018)
Delays are the global phenomena occur in the construction industry. Delays negatively affect project performance.Based on the category which causes delay, this research especially discussing about Non-Excusable Delays, in whichcontractors holds the responsibility for the delay. The purpose of this study is to analyze the relation between factors, and itseffects on delays in Manado. Model development is based on previous research and literature review. Primary data collectionwas done through distribution of questionnaires to project managers, site managers or implementers of contractors who had orare currently dealing with building construction projects in Manado. Data was analyzed using Partial Least Square. The resultsreveal that Improper Execution Planning directly and positively influence Construction Project Delay. On the other hand,Improper Execution Planning is influenced by Inefficient Site Management while Inefficient Site Management is significantlyinfluenced by Poor Contractor Competencies